P-0164: Sheathed vs. Standard Forceps: Does it matter for obtaining uncontaminated biopsy specimens of microbiota from the terminal ileum? - Dave, M; Johnson, L; Chaudhary, M; Funnell, J; Stidham, R; Walk, S; Young, V; Higgins, P (Inflammatory bowel diseases, 2009)
PurposeThe study of intestinal microbiota has been revolutionized by the use of PCR based methods including Terminal restriction fragment length polymorphism (TRFLP) analysis. A number of studies have been found associations between patients' intestinal microbiota and disease states. The microbiota of the neo-terminal ileum appears to be important in Crohn's disease recurrence. However, published microbiota studies have acquired human biopsy samples from stool, or using a standard unsheathed biopsy forceps, which could be contaminated with colonic bacteria when the forceps passes through the colonoscope channel. The goal of this study was to determine whether it is beneficial to use sheathed biopsy forceps (developed in our lab by modification of RJ4 Boston Scientific disposable biopsy forceps) vs. unsheathed (standard) biopsy forceps (RJ4 Boston Scientific disposable biopsy forceps) in order to obtain samples of microbiota from the terminal ileum that are not contaminated by colonic contents.SummaryWe recruited 30 consecutive subjects from the University of Michigan Medical scheduled for a clinically-indicated colonoscopy. Four (paired) biopsy specimens were then obtained from the adjacent locations in the terminal ileum using the sheathed and standard forceps. The tissue samples were immediately snap frozen in liquid nitrogen (-70 C) and transferred to the lab where microbiota present in the terminal ileum were characterized using the T-RFLP technique. Briefly, PCR amplification was performed using primers (8F and 1525R) targeting the 16S rRNA gene on each DNA sample. PCR products were then purified and digested with restriction enzyme Msp1. After digestion, the DNA fragments were separated on a automated sequence analyzer and analyzed using the K9 software program. The T-RFLP profiles obtained were normalized, Bray-Curtis distance matrices calculated, and a dendrogram was constructed. We calculated the Bray Curtis similarity index (BCI) of grouped samples (i.e. sheathed vs. unsheathed forceps) and compared it to the BCI for a ungrouped samples from the same patient, using each patient as his own control. If significant sample contamination occurred with the standard forceps, a sizable increase in microbial diversity should be detected and the BCI will be more for group X compared to group Y. In addition, species richness and a modified Shannon-Weiner Diversity Index were compared between unsheathed and sheathed samples.ResultsWe were able to obtain T-RFLP profiles from 27 patients. The difference in microbiota between patients was much greater than the variability within patients, as has been observed in previously published studies. Non-IBD patients had distinct individual ileal microbiota. There was not a significant difference between the ungrouped vs. between-group BCI. TTThe mean species richness for sheathed vs. unsheathed forceps was 601.7 and 602.1 (t-test p= 0.935) respectively. The mean modified Shannon- Weiner diversity was 7.41 vs. 7.42 (t-test p= 0.936) for sheathed vs. unsheathed forceps. However, there were 4 patients in whom a difference was detected in these indices.ConclusionThe overall microbial diversity was not significantly different between samples obtained with the sheathed and unsheathed forceps. Sheathed forceps do not appear to be generally required for microbiota sample collection from the terminal ileum.